Diseño del componente de seguridad industrial del SG-SST de la empresa Disenia S.A.S. (2021)
Finally, the MML methodology suggests that the analytical structure be reorganized, an expansion is carried out and the indicators, means of verification and assumptions related to each of the objectives set out in the diagram in figure 6 are defined. It describes in a simple way each of the goals, procedures and products necessary for the realization of the project.